ANALISIS MAKNA PADA LAGU SENKOU HANABI KARYA HONEYWORKS - Diah Krisnayanti Kadek Ayu; Anak Agung Ayu Dian Andriyani (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2025)
This study aims to determine the meaning of the song "senkou hanabi" by HONEYWORKS. This type of research is qualitative. The data source used in this study is one of the songs by HONEYWORKS entitled senkou hanabi. The data that has been obtained are analyzed using Riffaterre's semiotic theory. Methods and techniques of data collection in this study using the method of document study and literature study. Methods and techniques of data analysis using qualitative methods described by informal methods, namely by describing ordinary words in Indonesian that are easy to understand. The results of the semiotic research obtained in the song senkou hanabi are life, and there is a symbolic figure of speech in the form of senkou hanabi and also hotaru, both of which are symbolized as short life.